2014
DOI: 10.1007/s00464-014-4021-9
|View full text |Cite
|
Sign up to set email alerts
|

Early post-operative weight loss after laparoscopic sleeve gastrectomy correlates with the volume of the excised stomach and not with that of the sleeve! Preliminary data from a multi-detector computed tomography-based study

Abstract: MDCT is a good method to measure gastric volume before and after LSG. Early post-operative weight loss (3 months) correlates well with the volume of the excised stomach but not with that of the gastric sleeve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
0
27
1
Order By: Relevance
“…We found records of 428 patients from the 10 included studies studying the correlation of RGV after sleeve gastrectomy with weight loss. Table 1 shows the important characteristics of these studies 9,10,13‐20 . The mean age and BMI of the patients were 38.57 years and 44.99 kg/m 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found records of 428 patients from the 10 included studies studying the correlation of RGV after sleeve gastrectomy with weight loss. Table 1 shows the important characteristics of these studies 9,10,13‐20 . The mean age and BMI of the patients were 38.57 years and 44.99 kg/m 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported oversewing of the staple line, 16,17,20 and in one study, sewing of omentum to the staple line was performed 13 . In another study, no staple line reinforcement was used 9 . In majority of the included studies, CT volumetry was performed using an effervescent solution of 4 mg of Sodium Bicarbonate granules or tartaric acid/ sodium hydrogen carbonate salts to distend the stomach remnant with gas.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances in the CT technology and three-dimensional (3D) post-processing software have enabled new exciting possibilities like CT-based endoscopic images [virtual endoscopy (VE)] 1 as well as allowed accurate staging for neoplastic diseases of the stomach 2 and predict the post-operative weight loss for patients undergoing bariatric surgery. 3 It is very important for a radiologist to understand the appropriate gastric imaging protocol, since the acquisition of appropriate CT images requires patient fasting, adequate gastric distension and a negative intraluminal contrast agent. This article describes the basic principle and protocol for multidetector CT (MDCT) of the stomach and reviews the role of CT for the diagnosis of various gastric pathologies and post-operative surveillance.…”
Section: Introductionmentioning
confidence: 99%